Zharaf Zaman dan Zharaf Makan dalam Bahasa Arab dan Keterangan Waktu dan Keterangan Tempat dalam Bahasa Indonesia: Perbandingan Bahasa - Latifa Islami Anuar; Yufni Faisol; Syahrial Syahrial (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
This article discusses the similarities and differences between zharaf zaman and zharaf makan in Arabic with an adverb of time and place in Indonesian. The method used in this study was a comparative analysis method that describes the zharaf zaman of zharaf makan in Arabic with an adverb of time and place in Indonesian. The similarities and differences between the two languages were then compared to each other in terms of their form and usage in sentences. The analysis concluded that there are similarities between the zharaf zaman with an adverb of time, which is in the form of a single word, idhafah and jar letters. Moreover, the difference between the two was found in its jamid and musytaq. The form of jamid and musytaq was only found in Arabic. In terms of its use in sentences, both the zharaf zaman and zharaf makan and adverb of time and place shared similarities and differences in terms of formation, nashab, its usage in question sentences and so forth.